(untitled) (Fiep Bulletin - online, 2011)
This work is part of an early poll, which has the theme: The ethics and morality in the use of school playing in online search - Corporate Culture and Education through Movement, Group of Interdisciplinary Research and Study of the Body and Movement that seeks to strengthen the scope and scientific initiative between academics and teachers, the School of Physical Education, Bachelor of Regional Integrated University of High Uruguay and Missions RS. It aims to analyze the participation of children in play schools in spare moments, intending to capture the ethical and moral from these experiences to catalog, map and make any interference, as well as help in building a responsible citizenship (social rules). The problem of knowledge that underpins this study is: You can check the games played by children and adolescents in free time options used ethical and moral? The theoretical methodology chosen for this research is descriptive, qualitative interpretive case study with. The collection of data that will be used in this investigation will be according to the theoretical and methodological foundations based on authors such as Hammersley Y Atkinson (1983), Bogdan Taylor Y (1996), Perez Serrano (1994), Cauduro (1998) , Cauduro (2004), Arnal et al (1992), among others. The analysis and interpretation of data will be made through the triangulation of data referenced by the authors cited. The screenplay of questionnaires and observations will be drawn from the recognition of the field of study (input field) and requires a qualitative (immersion in the ethos studied). The schools are to study two state schools in the periphery, both low-income, with different social problems. The indication of the schools was the responsibility of the researchers after talking with several managers of low-income schools.